Modelling the relationship between preschool competencies and school achievement in the Longitudinal Study of Australian Children - Ozolins, Clare; Buckley, Sarah; Reid, Kate; Khoo, Siek Toon (My University, 2013)
The focus on successful transitions from preschool contexts to the school environment has received substantial attention with recognition of the importance of early childhood environments in preparing children to achieve well at school. Children's' early number and language competencies are claimed to be highly predictive of school achievement, yet there are few studies which model these relationships longitudinally. There has also been a long standing recognition in developmental research that single indices of developmental outcomes offer poor explanatory power in comparison to interactions between combinations of predictors. Nonetheless, the tendency to focus on isolated processes and individual predictors is well-established in developmental research, although they tend to have only marginal predictive power for childhood outcomes. The availability of complex modelling techniques provides an opportunity to move beyond single indicators to consider the role of growth trajectories as predictors of developmental outcomes. Longitudinal data are rare in developmental research and the Longitudinal Study of Australian Children provides a unique opportunity to study the relationships between preschool competence measures (and the growth in these measures) in multiple domains (e.g., cognitive, social) and school achievement. In this context, the current study aims to explore the growth in children's academic competencies across the transition from preschool to school. In addition, we aim to model the degree to which developmental transitions differ for subgroups of children (e.g., according to socio-economic factors).
Keywords: Activities -- Children's activities; Children -- Early childhood; Education and Training -- School readiness; Childhood and child development; Learning, education and training; Activities; Children; Education and Training; School readiness; Early childhood; Children's activities; Childhood and child development; Learning, education and training